Effectiveness of a 'Workshop on Decluttering and Organising' programme for teens and middle-aged adults with difficulty decluttering: a study protocol of an open-label, randomised, parallel-group, superiority trial in Japan. Issue 6 (10th June 2017) - Aso, Yasuko; Yamaoka, Kazue; Nemoto, Asuka; Naganuma, Yuki; Saito, Masashige
Abstract : Introduction: Hoarding disorder can cause problems with work performance, personal hygiene, health and well-being. The disorder is a growing social problem in Japan. Having difficulty discarding rubbish, decluttering and organising can signal a future hoarding disorder, and early intervention is important. We developed an educational workshop on decluttering and organising for teens and adults with difficulty organising. The objective of this study is to evaluate the effectiveness of a workshop for reducing clutter and improving quality of life among younger people with difficulty decluttering and organising. Methods and analysis: An open-label, parallel-group, randomised controlled trial will be conducted among volunteers aged 12–55 years with mild difficulty decluttering and organising. Those in the intervention group will attend the workshop and receive a visit from a professional cleaning company to declutter their living space. The control group will have only the latter. The primary outcome will be the score on the Japanese version of the Saving Inventory-Revised. Secondary outcomes will be scores on the Clutter Image Rating Scale, the Japanese version of the Rosenberg Self-Esteem Scale and the Roles of Private Space Scale. The results will be examined for differences between the two groups in changes from baseline to 7 months. We will examine crude effects and adjust for gender and age using a general linear model for continuous variables and a logistic regression model for dichotomous variables. Sample size was calculated assuming a significance level of 5% (two tailed), a power of 80% and an effect size of 0.75. In total, 60 subjects (30 in each group) will be required. Ethics and dissemination: The study protocol has been approved by the Medical Ethical Committee of Teikyo University (No. 15-065). The findings will be disseminated widely through peer-reviewed publication and conference presentations. Trial registration number: UMIN000020568. Issue date: 16 January 2016.